Sudden Death from Cardiopulmonary Arrest on Arrival of a Patient with Pulmonary Tuberculosis: A Case Diagnosed by Postmortem CT and Autopsy. Issue 5 (22nd January 2018) - Yaguchi, Daizo; Ichikawa, Motoshi; Inoue, Noriko; Kobayashi, Daisuke; Shizu, Masato; Imai, Naoyuki; Watanabe, Kazuko
Abstract: Sudden death due to massive hemoptysis during management of tuberculosis occurs in a considerable number of patients. However, when massive airway hemorrhage occurs in a patient in whom tuberculosis has not been confirmed and a blood is not apparent externally on the face/body, it is difficult to immediately identify the cause of death as airway obstruction by tuberculous bleeding in the airway. We encountered an 83‐year‐old Japanese woman with her medical history included treatment of tuberculosis in her 20s who was in cardiopulmonary arrest on arrival (CPAOA), and the cause of sudden death could not initially be identified. Postmortem CT (PMCT) and autopsy revealed that the cause of sudden death was airway obstruction/asphyxia by tuberculous massive airway hemorrhage. Identification of the cause of death facilitated a subsequent active contact investigation and led to prevention of secondary tuberculosis infection.